2020
DOI: 10.1021/acsomega.0c02473
|View full text |Cite
|
Sign up to set email alerts
|

Formation Damage Induced by Water-Based Alumina Nanofluids during Enhanced Oil Recovery: Influence of Postflush Salinity

Abstract: Injecting nanofluids (NFs) has been proven to be a potential method to enhance oil recovery. Stranded oil is produced by wettability alteration where nanoparticles form a wedge film on pore wall surfaces, which is thought to shrink the pore space of the reservoir. Furthermore, ensuring the stability of the injected NF during the application is a major challenge. A low permeability reservoir and salinity of water make the response of NF injection to the formation damage more difficult. This article, therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…However, combing both the sonication and the magnetic stirring could prolong the stability of the nanofluid. Furthermore, Nguele et al [43] and later Ngo et al [47] reported that bubbling gas during the preparation could further enhance the stability regardless the type of base fluid (Figure 5).…”
Section: Enhancing the Stability Of Nanofluidmentioning
confidence: 96%
See 4 more Smart Citations
“…However, combing both the sonication and the magnetic stirring could prolong the stability of the nanofluid. Furthermore, Nguele et al [43] and later Ngo et al [47] reported that bubbling gas during the preparation could further enhance the stability regardless the type of base fluid (Figure 5).…”
Section: Enhancing the Stability Of Nanofluidmentioning
confidence: 96%
“…With the presence of salt at the interface, the excess surface concentration turns positive from which results a low contact angle (Figure 7a) and higher IFT (Figure 7b). An oil production scenario in which the salt concentration is large, the salting-out effect seems to prevail [47].…”
Section: Wettability and Ift Alterationmentioning
confidence: 99%
See 3 more Smart Citations